ANALYSIS OF SOURCES OF FINANCING PUBLIC DEBT AND ITS RISKS IN IRAQ AFTER 2003 EXTRACTED SEARCH - Prof. Dr. Jalil Kamel Ghaidan (Scholar Express Journals, 2023)
The problem of unilateral dependence (oil) on financing the general budget through oil revenues, which constitute a very high percentage with the decline of tax revenues and other revenues, leads to the consolidation of the rentier state in the Iraqi economy, which leads to continuous disturbances in the general budget and the achievement of a deficit due to continuous fluctuations In oil prices. In order to finance the budget deficit, the government resorts to borrowing, whether internal or external, which will create pressure on local resources and financial burdens to be borne by future generations. Additional revenue for the state as a result, and then exacerbate the problem of indebtedness. However, after 2003 and in light of economic openness to the outside world and increasing reliance on oil revenues to supplement the budget, we noticed the reality of the Iraqi economy only after the deepening in the rentier nature of the economy. There are no new directions for drawing up economic policies that aim to address structural imbalances and rebuild the structure of The bad economy and its removal from the impact of internal and external shocks.
Keywords: Internal public debt; internal public debt; public budget